Utilization of Prawn Waste as Pig Feed - Syam Mohan K M (Department of Animal Nutrition, College of Veterinary and Animal Sciences, 1991)
An investigation was carried out to assess the feeding value of prawn waste as a partial or complete replacement of unsalted dried fish in the rations for growing – finishing pigs. Thirty – two Large White Yorkshire weanling pigs with an average body weight of 9.1 kg were distributed randomly and uniformly as far as possible to four groups (Groups 1, 11, 111 and IV) of eight animals each, with regard to age, sex and body weight and housed in pairs of the same sex. The four dietary treatments A, B, C and D were allotted to the pigs in the groups 1, 11, 111 and IV respectively. Of the total protein, 25 per cent in the diets A, B and C and 12.5 per cent in the diet D were provided as animal protein. Unsalted dried fish was used as animal protein source in the diets C and D. Diet C formed the control diet. In the diets A and B, 50 per cent and 100 per cent replacements respectively of animal protein from unsalted dried fish were made using dried prawn waste. All the animals were maintained on the respective diets with 18 per cent total protein upto an average live weight of 50 kg and with 14 per cent protein till they attained a body weight of 70 kg or 8 months of age, whichever was earlier, when they were slaughtered to study carcass characteristics. The results indicated that diets containing prawn waste as an animal protein source promoted growth in pigs at a significantly lower rate (P < 0.01) when compared to the diets containing unsalted dried fish as animal protein source. The average daily gain obtained for pigs on dietary treatments A, B, C and D were 236 g, 200 g, 429 g and 416 g respectively. The poor growth performance of pigs maintained on diets A and B also reflected on the gain in body measurements and average age at slaughter. Pigs on diets C and D reached an average body weight of 70 kg at 205 days and 211 days of age respectively while those on diets A and B failed to attain 70 kg body weight even at 8 months of age. The results of the study on the digestibility coefficients of nutrients showed that replacement of animal protein at 50 per cent level in the ration with prawn waste increased the digestibility of dry matter and nitrogen – free extract whereas 100 per cent replacement with prawn waste decreased the digestibility of crude protein. Carcass characteristics like dressing percentage without head, half carcass weight, carcass length, backfat thickness, eye muscle area and weight of ham were adversely affected significantly by the inclusion of prawn waste in the rations as partial or complete replacement of unsalted dried fish. No significant difference could be observed in the growth rate, gain in body measurements, average age at slaughter and carcass characteristics of pigs when prawn waste replaced 50 and 100 per cent of the animal protein portion of the diets. An overall assessment of the results, indicated that incorporation of prawn waste in the ration of pigs as a partial or complete replacement of animal protein from unsalted dried fish did not promote appreciable growth and as such it has no significant value as a suitable animal protein source for feeding pigs.